Kemampuan Guru Sekolah Dasar di Kabupaten Keerom dalam Menyusun Karya Ilmiah Penelitian Tindakan Kelas: The Ability of the Primary School Teacher of Keerom Regency in Writing Scientific Paper of Class Action Research - Normawati Normawati (Balai Bahasa Provinsi Papua, 2020)
Since Law Number 14 2005 on Teacher and Lecturer was effective, teacher was pushed to improve their academic effort. One of this effort is writing a scientific paper of class action research (PTK). This study aims to (1) measure teachers’ ability in writing paper of class action research (2) analyze teacher’s error in writing scientific paper. There are 33 Primary School Teachers in Keerom Regency who propose their promotion in 2016 as the subject of this study. This study using qualitative dascriptive method based on quantitative data. The analysis result shows that on the whole mean score of teachers’ writing is 74.75 of 100. Then, all the writing acquire predicate as fair enough.